Ombres et lumières sur la Bretagne antique - Patrick Galliou (Pallas, 2009)
The archeological findings during the last half-century in Britain have shown that the actual « romanisation » of the island brought about by the Claudian conquest of 43 A.D. had been preceded by a phase of commercial and political contacts over the last century before our era. In the light of the same findings, the « romanisation » proper is found to be many-sided, non linear and presumably imperfect, its geography influencing the events which witnessed at the beginning of the Vth century the disruption of Roman order.